Macrophage-derived mir-100-5p orchestrates synovial proliferation and inflammation in rheumatoid arthritis through mTOR signaling - Huan Liu; Yuehong Chen; Yupeng Huang; Ling Wei; Jingjing Ran; Qianwei Li; Yunru Tian; Zhongling Luo; Leiyi Yang; Hongjiang Liu; Geng Yin; Qibing Xie (Journal of Nanobiotechnology, 2024)
Abstract Background Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by synovial inflammation, causing substantial disability and reducing life quality. While macrophages are widely appreciated as a master regulator in the inflammatory response of RA, the precise mechanisms underlying the regulation of proliferation and inflammation in RA-derived fibroblast-like synoviocytes (RA-FLS) remain elusive. Here, we provide extensive evidence to demonstrate that macrophage contributes to RA microenvironment remodeling by extracellular vesicles (sEVs) and downstream miR-100-5p/ mammalian target of rapamycin (mTOR) axis. Results We showed that bone marrow derived macrophage (BMDM) derived-sEVs (BMDM-sEVs) from collagen-induced arthritis (CIA) mice (cBMDM-sEVs) exhibited a notable increase in abundance compared with BMDM-sEVs from normal mice (nBMDM-sEVs). cBMDM-sEVs induced significant RA-FLS proliferation and potent inflammatory responses. Mechanistically, decreased levels of miR-100-5p were detected in cBMDM-sEVs compared with nBMDM-sEVs. miR-100-5p overexpression ameliorated RA-FLS proliferation and inflammation by targeting the mTOR pathway. Partial attenuation of the inflammatory effects induced by cBMDM-sEVs on RA-FLS was achieved through the introduction of an overexpression of miR-100-5p. Conclusions Our work reveals the critical role of macrophages in exacerbating RA by facilitating the transfer of miR-100-5p-deficient sEVs to RA-FLS, and sheds light on novel disease mechanisms and provides potential therapeutic targets for RA interventions. Graphical abstract